How Issue Salience Pushes Voters to the Left or to the Right - Walgrave, Stefaan; Van Erkel, Patrick; Jennart, Isaïa; Lefevere, Jonas; Baudewyns, Pierre (Politics of the Low Countries, 2025)
Recent research demonstrates that political parties in western Europe are generally structured along one dimension – and often take more or less similar ideological positions on the economic and cultural dimension – whereas the policy preferences of voters are structured two dimensionally; a considerable part of the electorate combines left-wing stances on one dimension with right-wing stances on the other. These ideologically ‘unserved’ voters are the main focus of this study. Using data from a large-scale survey in Flanders and Wallonia, we demonstrate how the salience of the two dimensions explains whether these unserved voters ultimately end up voting for a right-wing or a left-wing party. Specifically, we show that these voters elect a party that is ideologically closest on the dimension that they deem most important at that time. To summarise, the findings of this study confirm that salience is a key driver of electoral choice, especially for cross-pressured voters.